2019
DOI: 10.1021/acscatal.9b00099
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Increased Efficiency for Electroreduction of Carbon Monoxide Using Supported Polycrystalline Copper Powder Electrocatalysts

Abstract: Many electrocatalysts can efficiently convert CO2 to CO. However, the further conversion of CO to higher-value products was hindered by the low activity of the CO reduction reaction and the consequent lack of mechanistic insights for designing better catalysts. A flow-type reactor could potentially improve the reaction rate of CO reduction. However, the currently available configurations would pose great challenges in reaction mechanism understanding due to their complex nature and/or lack of precise potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
133
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(144 citation statements)
references
References 57 publications
4
133
2
Order By: Relevance
“…While these results seem to suggest a quite feasible way to promote CO 2 electroreduction towards more valuable products, that is, to increase the electrolyte pH, major inconsistencies exist between this hypothesis and the current mechanistic understanding of the formation of C 2+ products . As revealed by recent experimental and computational investigations, the rate determining step (RDS) of C 2+ product formation is the dimerization of two CO ads through Langmuir–Hinshelwood process which does not include proton transfer . Thus, the C 2+ product formation rate is not expected to show such a strong dependence on the electrolyte pH.…”
Section: Introductionmentioning
confidence: 99%
“…While these results seem to suggest a quite feasible way to promote CO 2 electroreduction towards more valuable products, that is, to increase the electrolyte pH, major inconsistencies exist between this hypothesis and the current mechanistic understanding of the formation of C 2+ products . As revealed by recent experimental and computational investigations, the rate determining step (RDS) of C 2+ product formation is the dimerization of two CO ads through Langmuir–Hinshelwood process which does not include proton transfer . Thus, the C 2+ product formation rate is not expected to show such a strong dependence on the electrolyte pH.…”
Section: Introductionmentioning
confidence: 99%
“…[52] For all the electrodes tested in this work, the current densities increased with increasing potential, although the lower potentials (À 0.5 V and À 0.3 V vs Ag/AgCl) are not included in Table 2 because the current densities generated in those conditions were too low to make the calculations reliable. [17,51] The uncoated GDE prepared in this work generated higher current densities and increased methanol production than the pure CS : PVA MCE, with a FE for methanol of 40.11 % and 19.71 %, respectively. [17,51] The uncoated GDE prepared in this work generated higher current densities and increased methanol production than the pure CS : PVA MCE, with a FE for methanol of 40.11 % and 19.71 %, respectively.…”
Section: Electrochemical Reduction Of Comentioning
confidence: 91%
“…The decreasing FE to methanol with increasing potential and current density at higher overpotentials can be allocated to the HER as the dominating reaction. [17,51] The uncoated GDE prepared in this work generated higher current densities and increased methanol production than the pure CS : PVA MCE, with a FE for methanol of 40.11 % and 19.71 %, respectively. These results are attributed to the higher accessibility of CO 2 to the catalyst in the uncoated GDE, and confirmed that the membrane over-layer was posing an additional resistance to transport.…”
Section: Electrochemical Reduction Of Comentioning
confidence: 91%
See 2 more Smart Citations